An Analytic Study on the Possibility of Price Reduction in Iran’s Legal System - Ali Eslamipanah; Behzad Farjam; Hossein Eskandari (پژوهش‌نامه حقوق اسلامی, 2016)
The topic of this article is study on the possibility of applying of the rule of price reduction, as one of the buyer’s rights, in Iran’s legal system. Aforementioned rule, was predicted in article 50 of the convention on the international sale of goods (1980 Vienna), as an international model law and means that the buyer despite of delivering nonconforming good with the contract by the seller, accepted it and intended to restore the consideration of nonconforming sale. The results of this study indicate that despite the lack of an explicit forecast of this rule in juridical texts and Iranian’s laws, parallel institutions with this rule can be found in them that indicate willingness of founder and legislator to accept this rule. The authority to obtain compensation (Arsh) in the option of defect and to split the price in the option of discrimination, are from the domestic similar cases approved in line with the price reduction rule and has the same goal and function and in this respect can be taken into consideration.